EFFECT OF PENSION INVESTMENT ON FINANCIAL DEPTH IN NIGERIA: EMPIRICAL INVESTIGATION - OYEDOKUN, Godwin Emmanuel; AKINGUNOLA, Richard O.; SOMOYE, Russell O.C. (Annals of Spiru Haret University. Economic Series, 2022)
This study examined the effect of pension investment on financial dept in Nigeria. The study adopted an ex-post facto research design. The population of the study is 14 years of Nigeria economy from the year 2007-2020. Time-series data were sourced for this study which are entirely secondary data from the Pension Commission and the Central Bank of Nigeria (CBN) statistical bulletin, and the World development indicator (WDI) of the World Bank Database. Autoregressive Distributed Delay Limitation (ARDL) bounds testing approach was adopted to examine the long- and short-term relationships between the series, using Eview 12 version. The result of the hypothesis shows that there is evidence that pension investment in equities has positive relationship with financial deepening. This implies that increases in pension investment in equities will lead to increase in financial depth in Nigeria. In sharp contrast, pension investments in FGN securities, local money market securities and mutual funds have a negative relation with financial depth. This implies that increases in pension investments in FGN securities, local money market securities and mutual funds will lead to decrease in financial depth in Nigeria. The result also shows that in the short run that pension investments in equities and mutual funds have positive but insignificant relationship with financial depth, while FGN securities and local money market securities have negative and insignificant relationship with financial depth. The study then recommended that, to accelerate financial sector depth, it is necessary for the financial sector regulators and policymakers to strengthen the depth of banks asset, other financial institutions and financial markets through policies and reforms to attract more pension investment that will contribute to the development of Nigeria’s financial stance.